2013
DOI: 10.1007/s00520-013-2022-1
|View full text |Cite
|
Sign up to set email alerts
|

Delaying skeletal-related events in a randomized phase 3 study of denosumab versus zoledronic acid in patients with advanced cancer: an analysis of data from patients with solid tumors

Abstract: Purpose Bone complications of metastatic disease, including skeletal-related events (SREs), impair patients' functioning and quality of life. In a randomized, phase 3 trial of 1,776 patients with metastases from solid tumors (except breast or prostate) or multiple myeloma, denosumab was non-inferior to zoledronic acid (ZA) in delaying or preventing SREs. This ad hoc analysis reports outcomes in the subgroup of 1,597 patients with solid tumors, excluding patients with multiple myeloma. Methods Patients received… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
149
2
11

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 163 publications
(175 citation statements)
references
References 25 publications
13
149
2
11
Order By: Relevance
“…Finally, cases of positively adjudicated ONJ according to very strict criteria were only 89 (1.6 %)-37 (1.3 %) on zoledronic acid and 52 (1.8 %) on denosumab. Notably, in the three trials, there were 14 ONJ cases among 464 patients treated with an antiresorptive agent (zoledronic acid or denosumab) and antiangiogenic agents (3.0 %) versus 75 ONJ cases among 5,259 patients receiving zoledronic acid or denosumab without any antiangiogenic agents (1.4 %) [5]: This kind of data seems to enforce recent literature data suggesting possible higher ONJ risk from combination of antiresorptive and antiangiogenic agents [7,8].According to the paper by Saad et al [5], among 89 total adjudicated ONJ patients (treated either with zoledronic acid or denosumab) there were six RCC patients, out of a total number of enrolled RCC patients of 155 [1,4]. This 6/155 (3.9 %) ONJ frequency in RCC patients is more than twice as high, if compared with the entire patient population (1.6 %).…”
mentioning
confidence: 60%
See 3 more Smart Citations
“…Finally, cases of positively adjudicated ONJ according to very strict criteria were only 89 (1.6 %)-37 (1.3 %) on zoledronic acid and 52 (1.8 %) on denosumab. Notably, in the three trials, there were 14 ONJ cases among 464 patients treated with an antiresorptive agent (zoledronic acid or denosumab) and antiangiogenic agents (3.0 %) versus 75 ONJ cases among 5,259 patients receiving zoledronic acid or denosumab without any antiangiogenic agents (1.4 %) [5]: This kind of data seems to enforce recent literature data suggesting possible higher ONJ risk from combination of antiresorptive and antiangiogenic agents [7,8].According to the paper by Saad et al [5], among 89 total adjudicated ONJ patients (treated either with zoledronic acid or denosumab) there were six RCC patients, out of a total number of enrolled RCC patients of 155 [1,4]. This 6/155 (3.9 %) ONJ frequency in RCC patients is more than twice as high, if compared with the entire patient population (1.6 %).…”
mentioning
confidence: 60%
“…
Dear Editor, The paper by Henry et al published by Supportive Care in Cancer comparing efficacy of denosumab versus zoledronic acid in patients with bone metastases of advanced solid tumours [1] comes to integrate the original reports of three pivotal large randomized phase 3 trials [2][3][4], the publication by Saad et al about osteonecrosis of the jaw (ONJ) in those three trials [5], and the combined outcome analysis by Lipton et al [6].Henry et al[1] reported outcomes of the single trial conducted on patients with solid tumours (except breast or prostate cancers, object of other two trials) [2,3], excluding patients with multiple myeloma: This ad hoc analysis confirmed the superiority of denosumab in delaying or preventing skeletal-related events [1]. Amongst side effects, after a median (Q1, Q3) time on study of 6.7 (3.2, 13.0) and 6.4 (3.1, 12.9)months in the two groups, ONJ was reported in six denosumab arm patients (0.8 %) and in nine zoledronic acid arm patients (1.1 %).

We wish to underline some sparse data reported in the cited papers, focusing attention on occurrence of ONJ in patients with renal cell cancer (RCC) included in the trial.

In the summary ONJ analysis [5] of the above-mentioned three randomized trials comparing zoledronic acid and denosumab in patients with several cancer types and conducted between 2006 and 2009, it appears that an "Oral Event Identified as Potential ONJ" was registered in 276 patients out of 5,723 (4.8 %).

…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In 2011, denosumab was approved in Canada for reducing the risk of sres in patients with solid tumours and bone metastasis. The approval was based on demonstrated superiority, in three large randomized clinical trials that compared denosumab with zoledronic acid, for delaying first onset of sres [11][12][13][14] . However, efficacy might not be the only treatment characteristic considered during a physician's decisionmaking process; a medication's safety profile (that is, adverse events) and mode of administration can also play an important role.…”
Section: Introductionmentioning
confidence: 99%